Analisis Risiko Proses Fabrikasi Tangki Penyimpanan dengan Menggunakan Metode FMEA (Failure Mode and Effect Analysis) (Studi Kasus PT. Sarana Remaja Mandiri) - Aprilia, Anggraini; Triana, Masca Indra; Safitri, Dika Ayu (Jurnal Sains dan Teknologi (JSIT), 2025)
The fabrication process of storage tanks is one of the crucial stages in the manufacturing industry, particularly to ensure the quality, strength, and safety of tanks used for storing raw materials or final products. However, potential failures are often found that can reduce production quality. This study aims to identify the causes of failure and analyze their risk levels I n the storage tank fabrication process at PT. Sarana Remaja Mandiri using the Failure Mode and Effect Analysis (FMEA)method. Through the application of FMEA, risk assessment was conducted based on three main parameters severity, occurrence, and detection which were then used to calculate the Risk Priority Number (RPN) to deterine improvement priorities. The results of the study show that there are 19 failure factors occurring in the marking, cutting, bevel, and rolling stages, each with different levels of risk. The risk analysis revealed that the RPN values across all fabrication stages range from 27 to 105. The highest RPN value of 105 was found in factor B5 during the cutting process, which indicates the highest level of risk and should be prioritized for corrective actions, followed by material cutting errors due to incorrect plate identification. This study is expected to provide insight into the importance of developing a more comprehensive risk analysis approach as an effort to improve the quality of production processes and strengthen risk control in the manufacturing industry.